Bortezomib-based induction followed by stem cell transplantation in light chain amyloidosis: results of the multicenter HOVON 104 trial - Minnema, Monique C.; Nasserinejad, Kazem; Hazenberg, Bouke; Hegenbart, Ute; Vlummens, Philip; Ypma, Paula F.; Kröger, Nicolaus; Wu, Ka Lung; Kersten, Marie Jose; Schaafsma, M. Ron; Croockewit, Sandra; Waal, Esther de; et al. (Haematologica, 2019)
This prospective, multicenter, phase II study investigated the use of four cycles of bortezomib-dexamethasone induction treatment, followed by high-dose melphalan and autologous stem cell transplantation (SCT) in patients with newly diagnosed light chain amyloidosis. The aim of the study was to improve the hematologic complete remission (CR) rate 6 months after SCT from 30% to 50%. Fifty patients were enrolled and 72% had two or more organs involved. The overall hematologic response rate after induction treatment was 80% including 20% CR and 38% very good partial remissions (VGPR). Fifteen patients did not proceed to SCT for various reasons but mostly treatment-related toxicity and disease-related organ damage and death (2 patients). Thirty-one patients received melphalan 200 mg/m2 and four patients a reduced dose because of renal function impairment. There were no deaths related to the transplantation procedure. Hematologic responses improved at 6 months after SCT to 86% with 46% CR and 26% VGPR. However, due to the high treatment discontinuation rate before transplantation the primary endpoint of the study was not met and the CR rate in the intention-to-treat analysis was 32%. Organ responses continued to improve after SCT. We confirm the high efficacy of bortezomib-dexamethasone treatment in patients with AL amyloidosis. However, because of both treatment-related toxicity and disease characteristics, 30% of the patients could not proceed to SCT after induction treatment. (Trial registered at Dutch Trial Register identifier NTR3220).
Published ahead of print on March 28, 2019
Gesehen am 09.12.2019